Lecture capture and peer working: exploring study practices through staff-student partnerships - Geraint Evans; Karl Luke (Association for Learning Technology, 2020)
As lecture capture technology and practice become ever more widespread in UK universities there is a growing body of literature that assesses the impact of these changes. However, there is still much to be understood about lecture capture and the full impact on student learning, especially in different institutional and subject contexts. This article describes two projects from a UK Russell Group University that worked in partnership with students to gain insights into the student experience regarding lecture capture. The article highlights insights gained in terms of how and why students use lecture recordings. This article focuses on one area in particular which has been less reported and warrants further investigation - students' use of lecture recordings in collaborative settings. The article considers some practical implications of such insights and argues that a nuanced understanding regarding the way students use lecture recordings for learning is required. The article also highlights how educationists can harness student partnerships to further our understanding of the complex interplays between technology and student learning.